Literary Festival as a Space for Tourism Literature: An Analysis of the Borobudur Writers and Cultural Festival - Ivan Adilla; Roma Kyo Kae Saniro; Bayu Ade Prabowo; Andina Meutia Hawa; Putri Ayiendra Dinanti (Raja Zulkarnain Education Foundation, 2025)
Contemporary cultural tourism increasingly emphasizes narrative- and knowledge-based experiences, thus literature plays a strategic role as a medium for shaping destination meaning. In this context, literary festivals have the potential to function as tourism literary practices that integrate texts, places, and cultural experiences. This article aims to examine the Borobudur Writers and Cultural Festival as a tourism literary practice through a literary festival and explain its role in building literary and cultural-based tourism experiences. This research uses a qualitative approach with a descriptive-interpretive design. Data collection tools are sourced from documentation of the Borobudur Writers and Cultural Festival for the 2017–2024 period, covering the festival's theme, location, core program, and value orientation. Analysis is conducted through identification, classification, and interpretation of data using the theoretical framework of tourism literature and literary festival theory. The results show that the Borobudur Writers and Cultural Festival consistently places literary themes as the main narrative of tourism, positions the place as a literary place, and builds a knowledge-based tourism experience. The festival's thematic evolution demonstrates a shift from a symbolic-textual approach to heritage-based tourism literature and destination networks through the concept of a moving festival. The festival also expands the literary experience through intellectual figures, artistic transformations, and public academic dialogue.